The best of the best : becoming elite at an American boarding school - Gaztambide-Fernandez, Rubén A., 1971- (IET telecommunications series, 2009)
For two years, Rubén Gaztambide-Fernández shared the life of what he calls the "Weston School," an elite New England boarding school. Vividly describing the pastoral landscape and graceful buildings, the rich variety of classes and activities, and the official and unofficial rules that define the school, The Best of the Best reveals a small world of deeply ambitious, intensely pressured students. For Gaztambide-Fernández, Weston is daunting yet strikingly bucolic, inspiring but frustratingly incurious, and sometimes - especially for young women - a gilded cage for a gilded age.